2016
DOI: 10.1523/jneurosci.0898-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Olig2-Targeted G-Protein-Coupled Receptor Gpr17 Regulates Oligodendrocyte Survival in Response to Lysolecithin-Induced Demyelination

Abstract: Demyelinating diseases, such as multiple sclerosis, are known to result from acute or chronic injury to the myelin sheath and inadequate remyelination; however, the underlying molecular mechanisms remain unclear. Here, we performed genome occupancy analysis by chromatin immunoprecipitation sequencing in oligodendrocytes in response to lysolecithin-induced injury and found that Olig2 and its downstream target Gpr17 are critical factors in regulating oligodendrocyte survival. After injury to oligodendrocytes, Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 54 publications
11
81
1
1
Order By: Relevance
“…Znf488 (also known as Zfp488), which is expressed in the same regions as Olig2 [29,30], did not have a significant effect on GPR17 expression (Fig 1E, lanes 1 and 4). These data supported the idea that GPR17 expression is targeted by Olig2 [28], and becomes exclusive to the floor plate as development progresses.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Znf488 (also known as Zfp488), which is expressed in the same regions as Olig2 [29,30], did not have a significant effect on GPR17 expression (Fig 1E, lanes 1 and 4). These data supported the idea that GPR17 expression is targeted by Olig2 [28], and becomes exclusive to the floor plate as development progresses.…”
Section: Resultssupporting
confidence: 83%
“…Next we explored the upstream transcription factors that induce GPR17 expression. Since GPR17 requires Olig1 for its expression [27] and is one of the target genes of Olig2 during oligodendrocyte development [28], we assessed if the overexpression of an Olig-type transcription factors could induce the GPR17 transcript. To address this, we prepared intermediate neural explants that were electroporated with the Olig2 expression plasmid, and determined the GPR17 expression level by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Additional upregulated local networks identified in l‐OPCs included genes encoding cell–cell adhesion proteins, including neuroligins and neurexins (NLGN4X, NRXN1) and their interacting partner the leucine‐rich repeat transmembrane protein LRRTM1 (Reissner, Runkel, & Missler, ). Further, we detected upregulation of local networks associated with leukotriene signaling, implicated in OL survival (Ou et al, ), including the receptor GPR17, and glutamate signaling, including metabatropic receptor GRM5, and AMPA type glutamate receptor subunits, GRIA2 and GRIA3, implicated in OPC maturation and functional diversification during development (Deng, Wang, Rosenberg, Volpe, & Jensen, ; Luyt, Varadi, Durant, & Molnar, ; Spitzer et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Expression analysis indicated that GPR17 was largely restricted to the oligodendrocyte lineage, and it was found that overexpression of GPR17 inhibited oligodendrocyte differentiation, whereas its abrogation accelerated oligodendrocyte differentiation and thus myelination (Chen et al, ). Importantly, a recent study indicated that pharmacological inhibition of GPR17 using pranlukast accelerated oligodendrocyte differentiation following toxin‐mediated demyelination, as did genetic abrogation of GPR17 (Ou et al, ). However, pranlukast does not specifically act on GPR17 (Grossman et al, ), but identification of a specific antagonist of GPR17 may represent a viable therapeutic option for enhancement of remyelination in the future.…”
Section: Hypothesis‐driven Approaches and Identification Of Strategiementioning
confidence: 99%